Assessment of Platelet Mitochondrial Respiration in a Pediatric Population: A Pilot Study in Healthy Children and Children with Acute Lymphoblastic Leukemia - Theia Lelcu; Anca M. Bînă; Maria D. Dănilă; Călin M. Popoiu; Oana M. Aburel; Smaranda T. Arghirescu; Claudia Borza; Danina M. Muntean (MDPI AG, 2021)
Characterization of mitochondrial respiration in peripheral blood cells has recently emerged as a potential biomarker for the assessment of the severity of hematological malignancies (HM) in adults. Whether changes in platelet respiratory function occur in children with or without HM it is unknown. The present pilot study was double-aimed: (i) to investigate whether platelet respiration is age-dependent in non-HM children and (ii) to assess the platelet mitochondrial respiration in children with newly diagnosed acute lymphoblastic leukemia (ALL). Blood samples obtained from age-grouped children (10-11, 13-14 and 16-17 years) with non-HM and children with ALL (10-11 years) were used to isolate platelets via differential centrifugation. High-resolution respirometry studies of isolated platelets were performed according to a protocol adapted to evaluate complex I and II-supported respiration. An age-related decrease in respiration was observed in the non-HM pediatric population and had comparable values for the 13-14 and 16-17 years. groups. In children with ALL, a significant increase in C I-supported active respiration and decrease in maximal noncoupled respiration were found at the disease onset. In conclusion, in a pediatric population, platelet mitochondrial respiration is age-dependent. Platelet respiratory dysfunction occurs in children with newly-diagnosed ALL, an observation that warrants further investigation of this change as a disease biomarker.